Isthmin 2 is Decreased in Preeclampsia and Highly Expressed in Choriocarcinoma: A Prospective Cross-sectional Study - Cynthia Martinez; Javier González-Ramírez; María E. Marín; Gustavo Martínez-Coronilla; Vanessa I. Meza-Reyna; Rafael Mora; Raul Díaz-Molina (Emerging Trends in Disease and Health Research Vol. 9, 2022)
Isthmin 2 (ISM2) is a protein that is almost exclusively expressed in the human placenta. There has been no previous study that looked into this protein in preeclampsia or choriocarcinoma. A prospective, cross-sectional study of women with preeclampsia, gestational hypertension, and normotensive pregnancy was carried out. We measured serum concentrations of ISM2 protein and performed immunohistochemistry in placenta tissues. In addition, we compared ISM2 immunohistochemistry in choriocarcinoma samples to lung, prostate, colon, stomach, and breast cancer tissues. A total of 81 individuals were enrolled in the study, 30 of whom had preeclampsia, 21 of whom had gestational hypertension, and 30 of whom were healthy controls. When compared to the control group, the ISM2 protein was shown to be lower in preeclampsia patients (P ¼ 0.036). Immunohistochemistry validated these findings. The ISM2 protein was also shown to be overexpressed in choriocarcinoma. Our findings imply that ISM2 has an angiogenic function. Its lower serum level in our preeclampsia patients could imply that it is implicated in the disease’s aetiology; on the other hand, its high expression in choriocarcinoma suggests that ISM2 may be involved in the angiogenesis of this and other malignancies.